Regenerative Medicine Therapies for Osteoarthritis and Cartilage - Alhomrani, Dr. Majid (Asian Journal of Pharmaceutics (AJP), 2022)
Osteoarthritis (OA) has a high burden and impact on society as it affects the quality of life of both young and older patients. OA is a degenerative joint disease characterized by the degeneration of articular cartilage. This cartilage is an avascular, unique matrix composed of chondrocyte cells, which can resist compression and redistribute loads but have poor self-regenerative capacity. Numerous types of treatment are available, such as non-pharmacology treatments involving diet, physiotherapy, exercise, and pharmacological which include different types of drugs. None of these two types has proven to be the ideal treatment, only symptomatic treatment. Total knee replacement is the final and only treatment available and used only when the other types of treatment fails. The intra-articular injection is an alternative treatment for OA, due to the localized nature of the disease. Various types of blood products are currently used, including platelet-rich plasma and orthokine to alert the inflammation response and enhance the healing process. Recently, regenerative treatments have widely been introduced to overcome the limitations of current treatments. Mesenchymal Stromal Cells (MSCs), which can differentiate into chondrocytes, are used to regenerate articular cartilage. In addition, the improvements in tissue engineering technology such as the use of different types of the scaffold as well as blood product and growth factors with MSC have had a great impact in treating OA and regenerating cartilage. This review will discuss the pathogenesis of OA and describes the current clinical management to treat the OA.